Sarcoma Assessment Measure-Paediatric Version (SAM-Paeds): development of a disease-specific patient reported outcome measure for children with sarcoma - Rachel M. Taylor; Sophie-Anne Purnell; Sian Hocking; Rachael Windsor; Craig Gerrand; Meriel Jenney; Madeleine Adams (Journal of Patient-Reported Outcomes)
Abstract Purpose Sarcomas account for approximately 10–15% of all cancer in children aged ≤ 16. Poorer health-related quality of life (HRQoL) is recorded in comparison to other cancers; however, these studies are limited by generic HRQoL measures not being specific to patients with sarcoma. The aim of this study was to develop paediatric version of the Sarcoma Assessment Measure (SAM). Methods This mixed methods study comprised three stages: item generation, item reduction and establishing content validity. Children aged 8–16 years and parents of children aged 0–16 years with a diagnosis of sarcoma and within 5 years of completion of treatment were invited to participate. Results A total of 29 children and 38 parents from three sites participated in the study. Content analysis of the interview transcripts identified 277 post-diagnosis experience statements of which 128 ‘items’ were included in an Item Reduction Questionnaire, grouped into six domains; physical, disability and inclusion; impact of diagnosis; emotional, impact on family, education. Items with a mean score < 5 and a content validity index of < 0.75 were removed. The final version of SAM-Paeds comprises 33 items (parent version) and 21 items (child version). Conclusion This study has developed the first disease-specific HRQoL measure for paediatric sarcoma patients. SAM-Paeds is planned for inclusion within international sarcoma clinical trials and will be validated alongside current generic measures. Developed with the same methodology as the adult SAM questionnaire will facilitate the assessment of QoL longitudinally to assess the long-term impact of the diagnosis and treatment of sarcoma in childhood.